2014
DOI: 10.1007/s11192-014-1432-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of public funding in nanotechnology scientific production: Where Canada stands in comparison to the United States

Abstract: Document publié chez l'éditeur commercial AbstractThis paper presents cross-country comparisons between Canada and the United States in terms of the impact of public grants and scientific collaborations on subsequent nanotechnology-related publications.In this study we present the varying involvement of academic researchers and government funding to capture the influence of funded research in order to help government agencies evaluate their efficiency in financing nanotechnology research. We analyze the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…To further understand how government research funding and scientific networks influence research publications in NST, a cross-country comparison between Canada and the USA was carried out (Tahmooresnejad et al, 2015). To explore the impact of funding on scientific papers and to reflect how NST research grants influence researchers' productivity, the authors used econometric methods.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To further understand how government research funding and scientific networks influence research publications in NST, a cross-country comparison between Canada and the USA was carried out (Tahmooresnejad et al, 2015). To explore the impact of funding on scientific papers and to reflect how NST research grants influence researchers' productivity, the authors used econometric methods.…”
Section: Related Workmentioning
confidence: 99%
“…The third notion deserving special mention is leadership related to the collaborative partnership and the position of scientists/institutions/countries in scientific networks as determinant for the quantity and quality of papers (Ni et al, 2011;Tahmooresnejad et al, 2015). We use the term "leadership" as defined by the Committee of Medical Journal Editors (International Committee of Medical Journal Editors, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…1 The studies on research funding within the research on research literature investigate funding allocation/peer review; research assessment; funding priorities and agenda setting; changing landscape of research funding; policy, practical or academic relevance/ effectiveness of funding; productivity and funding; research collaborations. Such literature often focuses either on the funding for specific field of studies (Grant & Buxton, 2018;Tahmooresnejad et al, 2015) and/or a specific national context (Haake & Silander, 2021;Meroka & Ojwang, 2018). There are also studies which take a broader multi-country/ worldwide view (Curry et al, 2020;Thomas et al, 2020;Whitley et al, 2018).…”
Section: Research Fundingmentioning
confidence: 99%
“…[10] performed an econometric study focused on 68 universities and observed no significant relation between funding and research quality. However, [11] who performed a cross country analysis between the US and Canada observed a positive impact of funding on the quality of nanotechnology publications. Following this, [12] conducted an extension study of both previous study and reported that there is significant positive impact of funding on the productivity of the researchers.…”
Section: Literature Reviewmentioning
confidence: 99%